Composite phosphate positive electrode material and preparation method and application thereof
Through ball milling treatment and two-stage sintering technology, the problems of poor carbon coating quality and low compaction density of the phosphate-based positive electrode material are solved, and the particle size uniformity and performance are improved, and the electrochemical performance of the material is improved.
Patent Information
- Application Number
- CN202411338473.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing phosphate-based positive electrode materials have poor carbon coating quality, low compaction density and small specific capacity, which leads to insufficient performance in actual applications.
The composite phosphate-based positive electrode material was used to obtain a powdered precursor through ball milling and perform two-stage sintering to control the particle size to be normally distributed, ensuring that the thickness of the carbon cladding layer is between 2.0 and 3.0 nm and the variance is between 0.01 and 0.30. Improve compaction density and specific capacity.
The particle size uniformity and compaction density of the composite phosphate-based positive electrode material are achieved, and the electronic conductivity and electrochemical performance of the material are improved, including discharge capacity and Coulomb efficiency.
Smart Images

Figure CN119275261A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion battery positive electrode materials, and in particular, relates to composite phosphate positive electrode materials and preparation methods and applications thereof. Background Art
[0002] With the continuous development of lithium-ion battery technology, people have higher requirements for the energy density and low-temperature performance of phosphate-based cathode materials. Phosphate-based cathode materials are commonly used with lithium iron phosphate and lithium iron manganese phosphate. The structures of these two materials are both olivine-type structures, and both have the same theoretical specific capacity and good safety performance. Among them, due to the presence of Mn element, the voltage platform of lithium iron manganese phosphate is higher than that of lithium iron phosphate. Therefore, lithium iron manganese phosphate has a higher energy density. Its energy density is theoretically 10-20% higher than that of lithium iron phosphate, and it has better low-temperature performance. Based on the above advantages, lithium iron manganese phosphate has received extensive attention and research from academia and industry in recent years, and has high application potential.
[0003] The voltage platform of lithium iron manganese phosphate is affected by the proportion of manganese in the material. The higher the proportion of manganese, the more obvious the voltage platform of the material is, and it has a higher energy density. Therefore, lithium iron manganese phosphate materials with high manganese content are one of the hot spots in the development of phosphate positive electrode materials. However, in the actual production process, lithium iron manganese phosphate materials are not easy to form large particles. Their particles are smaller than lithium iron phosphate, resulting in a lower compaction density of lithium iron manganese phosphate materials than lithium iron phosphate. Moreover, the higher the manganese content in the material, the more difficult it is for the particles of the material to grow. These factors greatly affect the energy density of the material. Therefore, the particle size of lithium iron manganese phosphate material is one of the key factors affecting its performance and application.
[0004] Currently, phosphate-based positive electrode materials are mainly prepared by high-temperature solid-phase sintering methods. However, the particle size and particle distribution of the phosphate-based positive electrode materials obtained by the conventional high-temperature solid-phase sintering method are uneven, and the carbon coating uniformity is poor, resulting in poor carbon coating quality, low compaction density, and small specific capacity of the phosphate-based positive electrode materials, which is not conducive to wide application. Summary of the invention
[0005] The purpose of the present application is to provide a composite phosphate-based positive electrode material and a preparation method and application thereof, aiming to solve the problems of poor carbon coating quality, low compaction density and small specific capacity of phosphate-based positive electrode materials in the prior art.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a composite phosphate-based positive electrode material, comprising a phosphate-based positive electrode material core and a carbon coating layer, wherein the particle size of the composite phosphate-based positive electrode material is normally distributed, the thickness of the carbon coating layer is 2.0 to 3.0 nm, and the variance is 0.01 to 0.30.
[0008] In some embodiments, the chemical formula of the phosphate-based cathode material core is Li x Mn a Fe b M c PO4, 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1; M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
[0009] In some embodiments, the particle size of the composite phosphate positive electrode material is 180-230 nm, and the compaction density is greater than 2.37 g / cm 3 .
[0010] In a second aspect, the present application provides a method for preparing a composite phosphate-based positive electrode material, comprising the following steps:
[0011] Providing a precursor mixture of composite phosphate-based cathode materials;
[0012] The precursor mixture is ball-milled to obtain a powdered precursor, and the particle size of the powdered precursor is monitored in real time until it is normally distributed;
[0013] The powdered precursor is subjected to a two-stage sintering process to obtain a composite phosphate-based positive electrode material.
[0014] In some embodiments, the step of ball milling the precursor mixture to obtain a powdered precursor includes: ball milling the precursor mixture multiple times at a ball-to-material ratio of 5:1 to 15:1 and performing real-time monitoring to control the particle size of the powdered precursor to be normally distributed, and the particle size D 90 1.0~3.0μm.
[0015] In some embodiments, the ball milling process is performed at a rotation speed of 450-650 rpm, for 7-8 hours, for 3-5 times, and with a grinding ball diameter of 6-7 mm.
[0016] In some embodiments, the step of subjecting the powdered precursor to a two-stage sintering treatment includes: providing an inert gas atmosphere, heating the powdered precursor to 520-560°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 2-5 hours, and then heating to 720-780°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 8-12 hours.
[0017] In some embodiments, the step of providing a precursor mixture of a composite phosphate-based cathode material comprises: x Mn a Fe b M c PO4 obtains a lithium source, a manganese source, an iron source, a phosphorus source, and an M source, and then mixes them with a carbon source to obtain a precursor mixture; wherein M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce; 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1.
[0018] In some embodiments, the lithium source is any one of lithium carbonate, lithium acetate and lithium hydroxide.
[0019] In some embodiments, the manganese source is at least one of manganese dioxide, trimanganese tetraoxide, and manganese oxalate.
[0020] In some embodiments, the iron source is at least one of ferric phosphate, ferrous nitrate, ferrous oxalate dihydrate, and ferrous sulfate.
[0021] In some embodiments, the phosphorus source is at least one of ferric phosphate, monoammonium phosphate, and diammonium phosphate.
[0022] In some embodiments, the M source includes an oxide containing an M element.
[0023] In some embodiments, the carbon source is at least one of glucose, polyethylene glycol, citric acid, sucrose, glycine, and starch.
[0024] In some embodiments, the total mass of the precursor mixture is 100%, and the amount of the carbon source added is 5-10 wt%.
[0025] In a third aspect, the present application provides a positive electrode plate, which includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the above-mentioned composite phosphate positive electrode material or a composite phosphate positive electrode material prepared by the above-mentioned method for preparing the composite phosphate positive electrode material.
[0026] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the above-mentioned positive electrode sheets.
[0027] The composite phosphate positive electrode material provided in the first aspect of the present application comprises a phosphate positive electrode material core and a carbon coating layer, wherein the particle size of the composite phosphate positive electrode material is normally distributed, the finished particles are relatively large and the particle size is uniform, and the compaction density is significantly improved; and the carbon coating layer is uniformly coated on the surface of the core material, and the thickness of the carbon coating layer is moderate, which can not only improve the electronic conductivity of the positive electrode material, but also improve the electrochemical properties of the composite phosphate positive electrode material such as discharge capacity and coulomb efficiency.
[0028] The second aspect of the present application provides a method for preparing a composite phosphate-based positive electrode material. The preparation method ball-mills the mixed precursor mixture to obtain a powdered precursor, controls the particle size of the powdered precursor by controlling the conditions of the ball milling treatment, and monitors the particle size distribution curve of the powdered precursor in real time until it presents an approximate normal distribution curve, so as to obtain a finished product having a larger overall particle size, a moderate and uniform carbon coating thickness, and a high compaction density and specific capacity. The preparation method is simple and quick, does not require large-scale instruments and equipment, and is conducive to wide application.
[0029] The positive electrode plate provided in the third aspect of the present application comprises a positive electrode active layer comprising a composite phosphate-based positive electrode material having excellent carbon coating quality, high compaction density and high specific capacity, so that the obtained positive electrode plate has excellent cycle performance and capacity effect.
[0030] The secondary battery provided in the fourth aspect of the present application includes the above-mentioned positive electrode plate, and the positive electrode plate provided has excellent cycle performance and capacity effect, so the obtained secondary battery has high charge and discharge specific capacity, high cycle efficiency and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 This is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Example 1 of the present application.
[0033] Figure 2 This is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Example 2 of the present application.
[0034] Figure 3 This is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Example 3 of the present application.
[0035] Figure 4 It is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Comparative Example 1 of the present application.
[0036] Figure 5 It is the SEM analysis diagram (A) and the primary particle size statistics diagram (B) of the finished material provided in Comparative Example 2 of the present application.
[0037] Figure 6 It is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Comparative Example 3 of the present application.
[0038] Figure 7 It is the SEM analysis diagram (A) and primary particle size statistics diagram (B) of the finished material provided in Comparative Example 4 of the present application.
[0039] Figure 8 It is a diagram of the particle size distribution of precursor particles provided in Examples 1 to 3 and Comparative Examples 1 to 4 of the present application.
[0040] Fig. 9 This is a TEM characterization image of the finished material provided in Example 1 of the present application.
[0041] Fig.10 This is a TEM characterization image of the finished material provided in Example 2 of the present application.
[0042] Fig.11 This is a TEM characterization image of the finished material provided in Example 3 of the present application.
[0043] Fig.12 This is a TEM characterization image of the finished material provided in Comparative Example 1 of the present application.
[0044] Fig.13 This is a TEM characterization image of the finished material provided in Comparative Example 2 of the present application.
[0045] Fig.14 This is a TEM characterization image of the finished material provided in Comparative Example 3 of the present application.
[0046] Fig.15 This is a TEM characterization image of the finished material provided in Comparative Example 4 of the present application.
[0047] Fig.16 It is a charge and discharge curve diagram of the materials provided in Examples 1 to 3 and Comparative Examples 1 to 4 of the present application at 0.1C. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0049] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0050] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0051] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0052] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0053] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0054] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0055] A first aspect of an embodiment of the present application provides a composite phosphate-based positive electrode material, comprising a phosphate-based positive electrode material core and a carbon coating layer, wherein the particle size of the composite phosphate-based positive electrode material is normally distributed, the thickness of the carbon coating layer is 2.0 to 3.0 nm, and the variance is 0.01 to 0.30.
[0056] The composite phosphate-based positive electrode material provided in the first aspect of the embodiment of the present application comprises a phosphate-based positive electrode material core and a carbon coating layer, wherein the particle size of the composite phosphate-based positive electrode material is normally distributed, the finished particles are relatively large and the particle size is uniform, and the compaction density is significantly improved; and the carbon coating layer is uniformly coated on the surface of the core material, and the thickness of the carbon coating layer is moderate, which can not only improve the electronic conductivity of the positive electrode material, but also improve the electrochemical properties of the composite phosphate-based positive electrode material, such as the discharge capacity and coulombic efficiency.
[0057] Among them, the particle size of the composite phosphate positive electrode material is normally distributed, ensuring uniform particle size, which is beneficial to improving the overall compaction density and capacity of the material. In the embodiment of the present application, the particle size of the composite phosphate positive electrode material also includes the case of being approximately normally distributed. If the particle size distribution of the composite phosphate positive electrode material is significantly different from the normal distribution, it is easy to cause serious particle agglomeration and unclear boundaries, and it is not conducive to improving the compaction density of the material.
[0058] Further, the thickness of the carbon coating layer is 2.0 to 3.0 nm, and the variance is 0.01 to 0.30. The obtained carbon coating layer of the composite phosphate-based positive electrode material is uniformly coated and of moderate thickness, which helps to improve the overall capacity of the composite phosphate-based positive electrode material. The better the uniformity of the carbon coating layer, the larger the particles of the product, the thicker the coating layer, the smaller the particles, the thinner the coating layer, and the moderate particle size means that the carbon layer thickness is moderate. If the carbon coating layer is too thick, the transmission of lithium ions is hindered to a certain extent; if the carbon coating thickness is thin and uneven, it will cause the electrolyte to directly contact the core of the phosphate-based positive electrode material, increase the side reaction and cause the loss of capacity. In some specific embodiments, the thickness of the carbon coating layer includes but is not limited to 2.0 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3.0 nm, and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0059] In some embodiments, the chemical formula of the phosphate-based cathode material core is Li x Mn a Fe b M c PO4, 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1; M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce. The main purpose of adding the doping element M is to introduce certain defects into the crystal lattice of the phosphate-based positive electrode material, broaden the transmission channel of lithium ions, thereby improving the lithium ion mobility of the material, and then improving the performance of the material such as the discharge specific capacity.
[0060] Among them, the addition amount of the doping element M is 0.001 to 0.004 mol. The doping amount of the doping element M has a significant effect on the capacity and particle size of the positive electrode material. Within the range of the doping amount, the lithium ion mobility can be effectively improved, thereby improving the discharge specific capacity of the material; and ensuring that the obtained positive electrode material particles are of moderate size and can maintain a high compaction density. If the addition amount of the doping component is too much, on the one hand, it will make it difficult for the particles of the positive electrode material to grow, affecting the size and compaction density of the particles, and impurities will be formed inside the lattice of the material, affecting the capacity and rate performance of the material; if the addition amount is too little, the doping effect is not obvious, the capacity is very low, and it is not conducive to product application.
[0061] In some embodiments, the particle size of the composite phosphate positive electrode material is 180-230 nm, and the compaction density is greater than 2.37 g / cm 3In some specific embodiments, the particle size of the composite phosphate-based positive electrode material includes but is not limited to 180 nm, 190 nm, 200 nm, 205 nm, 210 nm, 215 nm, 220 nm, 225 nm, 230 nm, and other typical but non-limiting arbitrary point values or interval values between any two point values. In some specific embodiments, the compaction density of the composite phosphate-based positive electrode material includes but is not limited to 2.37 g / cm 3 , 2.38g / cm 3 , 2.39g / cm 3 , 2.40g / cm 3 , 2.41g / cm 3 , 2.42g / cm 3 , 2.43g / cm 3 , 2.44g / cm 3 , 2.45g / cm 3 wait.
[0062] In a second aspect, the present application provides a method for preparing a composite phosphate-based positive electrode material, comprising the following steps:
[0063] S01. Providing a precursor mixture of a composite phosphate cathode material;
[0064] S02. ball-milling the precursor mixture to obtain a powdered precursor, and monitoring the particle size of the powdered precursor in real time until it is normally distributed;
[0065] S03. The powdered precursor is subjected to a two-stage sintering process to obtain a composite phosphate-based positive electrode material.
[0066] The second aspect of the embodiment of the present application provides a method for preparing a composite phosphate-based positive electrode material. The preparation method ball-mills the mixed precursor mixture to obtain a powdered precursor, controls the particle size of the powdered precursor by controlling the conditions of the ball milling treatment, and monitors the particle size distribution curve of the powdered precursor in real time until it presents an approximate normal distribution curve, so as to obtain a composite phosphate-based positive electrode material with a larger overall particle size, a moderate and uniform carbon coating thickness, and a high compaction density and specific capacity. The preparation method is simple and quick, does not require large-scale instruments and equipment, and is conducive to wide application.
[0067] In step S01, a precursor mixture of a composite phosphate-based positive electrode material is provided.
[0068] In some embodiments, the step of providing a precursor mixture of a composite phosphate-based cathode material comprises: x Mn a Fe b M cPO4 obtains lithium source, manganese source, iron source, phosphorus source, M source, and then mixes with carbon source to obtain precursor mixture; wherein M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, Ce; 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1. In the preparation process of the precursor mixture, an additional carbon source is added, and a carbon coating layer is prepared in situ during the sintering process. The preparation of the carbon coating layer can improve the electronic conductivity of the material, avoid direct contact between the core material and the electrolyte, and improve the specific capacity of the material.
[0069] In some embodiments, the lithium source is any one of lithium carbonate, lithium acetate and lithium hydroxide.
[0070] In some embodiments, the manganese source is at least one of manganese dioxide, trimanganese tetraoxide, and manganese oxalate.
[0071] In some embodiments, the iron source is at least one of ferric phosphate, ferrous nitrate, ferrous oxalate dihydrate, and ferrous sulfate.
[0072] In some embodiments, the phosphorus source is at least one of ferric phosphate, monoammonium phosphate, and diammonium phosphate.
[0073] In some embodiments, the M source includes an oxide containing an M element.
[0074] In some embodiments, the carbon source is at least one of glucose, polyethylene glycol, citric acid, sucrose, glycine, and starch.
[0075] In some embodiments, the total mass of the precursor mixture is 100%, and the amount of carbon source added is 5-10wt%. If the amount of carbon source added is too much, the carbon content of the finished product will increase, the thickness of the carbon coating layer will be too large, and the specific surface area of the material will increase, affecting the processing of the material. In addition, the thick carbon layer will hinder the transmission of lithium ions; if the amount added is too little, the carbon coating is insufficient, the effect of improving the conductivity of the material is reduced, and at the same time, due to the low thickness of the coating layer, the side reactions between the material and the electrolyte increase, affecting the capacity.
[0076] In some specific embodiments, the total mass of the precursor mixture is 100%, and the added amount of the carbon source includes but is not limited to 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt% and the like typical but non-limiting arbitrary point values or the interval value between any two point values.
[0077] In step S02, the precursor mixture is ball-milled to obtain a powdered precursor, and the particle size of the powdered precursor is monitored in real time until it is normally distributed. In the process of pulverizing the precursor mixture, the precursor mixture is ground by a specific ball-milling method, and the particle size of the material is monitored and analyzed in real time after each ball-milling process until the particle size of the powdered precursor is normally distributed.
[0078] In some embodiments, the step of ball milling the precursor mixture to obtain a powdered precursor includes: ball milling the precursor mixture multiple times at a ball-to-material ratio of 5:1 to 15:1 and performing real-time monitoring to control the precursor mixture to be normally distributed and the particle size D 90 The ball milling speed is 450-650 rpm, the time is 7-8 hours, the number of times is 3-5 times, and the diameter of the grinding ball is 6-7 mm.
[0079] Among them, the ball-to-material ratio of ball milling is 5:1 to 15:1. A ball-to-material ratio in a suitable range is helpful to obtain a precursor with a suitable particle size. If the amount of grinding balls added is too much, the particle size of the obtained precursor will be too small, resulting in smaller particles of the finished product; conversely, if the amount of grinding balls added is too little, the particle size of the precursor will be too large, and the grinding will not be sufficient, and the particle size curve of the precursor will be unqualified. In some specific embodiments, the ball-to-material ratio of ball milling includes but is not limited to 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0080] In addition, the diameter of the grinding ball is 6-7 mm. If the diameter of the grinding ball is too large, during the grinding process, the stronger the impact force, the greater the stacking porosity of the grinding body, the faster the material flow rate, and the larger the particle size of the obtained product, which is not conducive to controlling the particle size of the product. In some specific embodiments, the diameter of the grinding ball includes but is not limited to 6 nm, 6.1 nm, 6.2 nm, 6.3 nm, 6.4 nm, 6.5 nm, 6.6 nm, 6.7 nm, 6.8 nm, 6.9 nm, 7.0 nm, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0081] Further, the rotation speed of the ball milling treatment is 450 to 650 rpm, and the time is 7 to 8 hours. The rotation speed of the ball milling treatment directly affects the motion state of the grinding balls in the ball mill. If the rotation speed of the ball milling treatment is too slow, the grinding balls will not rise high and will slide down, the crushing effect is very small, the particle size of the obtained powder precursor is too large and the grinding will be uneven, and the powder precursor with a normal particle size distribution cannot be obtained; if the rotation speed of the ball milling treatment is too fast, the grinding balls will be attached to the inner wall of the grinder and rotate with it, and the grinding effect on the raw material is weak. When the rotation speed of the ball milling treatment is controlled to be 450 to 650 rpm, the impact force and grinding effect on the precursor mixture are the greatest, and the crushing efficiency is the highest. In some specific embodiments, the rotation speed of the ball milling treatment includes but is not limited to 450 rpm, 500 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0082] The ball milling time is 7 to 8 hours. Controlling the ball milling time appropriately can ensure a better effect of the ball milling and a high degree of grinding. If the ball milling time is too low, the grinding effect is poor and the degree of grinding is weak; if the ball milling time is too high, the precursor particle size will be too small, resulting in the easy agglomeration of the finished particles. In some specific embodiments, the ball milling time includes but is not limited to 7 hours, 7.5 hours, 8 hours, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0083] The number of ball milling is generally 3-5 times, and the optimal number is 3 times; if the number of grinding is too large, the particle size of the precursor particles will be too small, and the particle size of the finished product will be difficult to grow; if the number of grinding is too small, the particle size distribution of the precursor will be uneven, affecting the performance of the finished product. In some specific embodiments, the number of ball milling includes but is not limited to 3 times, 4 times or 5 times.
[0084] Furthermore, during the ball milling process, real-time monitoring is performed to control the particle size of the powder precursor until it is normally distributed. 90 1.0~3.0μm. Control the precursor particle size D 90 The particle size of the finished product can be controlled within the target range when the particle size of the finished product meets the target, which helps to improve the compaction density and capacity. If the precursor particle size is too large, the particle size of the finished product will be too high, the particle size distribution curve will be non-normal, and the carbon coating will be thin and uneven, which will affect the compaction density and capacity of the material. If the precursor particle size is too small, it will be difficult for the finished product particles to grow, the carbon coating layer will be thicker, and the compaction density of the material will be low. In some specific embodiments, the particle size D of the precursor mixture is 90Including but not limited to typical but non-limiting arbitrary point values such as 1.0 μm, 1.5 μm, 2 μm, 2.5 μm, 3.0 μm, etc., or interval values between any two point values.
[0085] In step S03, the powdered precursor is subjected to a two-stage sintering process to obtain a composite phosphate-based positive electrode material.
[0086] In some embodiments, the step of subjecting the powdered precursor to a two-stage sintering treatment includes: providing an inert gas atmosphere, heating the powdered precursor to 520-560°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 2-5 hours, and then heating to 720-780°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 8-12 hours.
[0087] The main purpose of providing an inert gas atmosphere is to control the generation of no impurity molecules in the entire reaction environment, to ensure that there are no side reactions during the reaction process, and that no impurity molecules are generated. The inert gas atmosphere includes, but is not limited to, nitrogen atmosphere, argon atmosphere, helium atmosphere, etc.
[0088] The sintering treatment is a two-stage sintering treatment. The first stage of the sintering treatment is to heat the powdered precursor to 520-560°C at a heating rate of 3-8°C / min and calcine at a constant temperature for 2-5 hours. The low temperature and short time calcination conditions are mainly adopted. This stage is mainly the nucleation process of the phosphate-based positive electrode material, and the lattice of the phosphate-based positive electrode material is generated at this stage. At this stage, if the reaction temperature exceeds 560°C, side reactions will occur and impurities will be formed; if the temperature is lower than 520°C, the reaction energy is insufficient and it is impossible to fully react to form the lattice of the phosphate-based positive electrode material. The calcination time of this stage is controlled to be 2-5 hours. If the reaction time is too long, overburning will occur and impurities will be formed. If the reaction time is too short, the reaction is insufficient and the lattice of the phosphate-based positive electrode material cannot be fully reacted to form, and the lattice is unstable.
[0089] In a specific embodiment, under the sintering conditions of the first stage, the heating rate can be selected from typical but non-limiting arbitrary point values such as 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, or an interval value between any two point values; the heating temperature can be selected from typical but non-limiting arbitrary point values such as 520°C, 530°C, 540°C, 550°C, 560°C, or an interval value between any two point values; the heating time can be selected from typical but non-limiting arbitrary point values such as 2 hours, 3 hours, 4 hours, 5 hours, or an interval value between any two point values.
[0090] The second stage of sintering treatment is to heat to 720-780°C at a heating rate of 3-8°C / min and calcine at a constant temperature for 8-12 hours. It mainly adopts high temperature and long time calcination conditions. This stage is mainly a process of crystal nucleus growth and crystallinity enhancement. The particles of phosphate positive electrode material are further grown in this process. In this process, if the temperature exceeds 780°C, the temperature is too high and the particles will grow too large, affecting the capacity of the material, and may generate impurities. If the temperature is lower than 720°C, the temperature is too low and the crystallinity is poor, and the particle growth is insufficient. If the reaction time is too long, the particles will grow too large, affecting the capacity of the material, and may generate impurities. If the time is too short, the crystallinity is poor and the particle growth is insufficient.
[0091] In a specific embodiment, under the second stage sintering conditions, the heating rate can be selected from typical but non-limiting arbitrary point values such as 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, or an interval value between any two point values; the heating temperature can be selected from typical but non-limiting arbitrary point values such as 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, or an interval value between any two point values; the heating time can be selected from typical but non-limiting arbitrary point values such as 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, or an interval value between any two point values.
[0092] In a third aspect, the present application provides a positive electrode plate, including a current collector and a positive electrode active layer formed on the surface of the current collector, the positive electrode active layer including the above-mentioned composite phosphate-based positive electrode material or a composite phosphate-based positive electrode material prepared by the above-mentioned method for preparing the composite phosphate-based positive electrode material.
[0093] The positive electrode plate provided in the third aspect of the embodiment of the present application comprises a composite phosphate-based positive electrode material having excellent carbon coating quality, high compaction density and high specific capacity in the positive electrode active layer, so that the obtained positive electrode plate has excellent cycle performance and capacity effect.
[0094] In some specific embodiments, the preparation method of the positive electrode sheet includes the following steps: mixing a composite phosphate-based positive electrode material, a conductive agent and a binder to obtain a mixed slurry; coating the mixed slurry on the surface of the current collector, and then performing post-processing such as drying, rolling, and die cutting to obtain a positive electrode sheet.
[0095] In some embodiments, the total mass of the positive electrode active layer is 100%, and the composite phosphate positive electrode material accounts for 90wt% to 95wt% of the total mass of the positive electrode active layer. The content of the composite phosphate positive electrode material can be 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, etc., which are typical but not limiting contents.
[0096] In some embodiments, the total mass of the positive electrode active layer is 100%, and the conductive agent accounts for 1wt% to 5wt% of the total mass of the positive electrode active layer. The content of the conductive agent can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., which are typical but not limited. The conductive agent is selected from at least one of graphite, carbon black, acetylene black, graphene, carbon fiber and carbon nanotubes.
[0097] In some embodiments, the total mass of the positive electrode active layer is 100%, and the binder accounts for 1wt% to 5wt% of the total mass of the positive electrode active layer. The content of the binder can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% and other typical but non-limiting contents. Among them, the binder is selected from at least one of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.
[0098] Furthermore, the current collector includes but is not limited to any one of copper foil and aluminum foil.
[0099] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the above-mentioned positive electrode sheets.
[0100] The secondary battery provided in the fourth aspect of the embodiment of the present application includes the above-mentioned positive electrode plate, and the provided positive electrode plate has excellent cycle performance and capacity effect, so the obtained secondary battery has high charge and discharge specific capacity, high cycle efficiency and excellent performance.
[0101] Among them, the negative electrode plate, separator and electrolyte of the secondary battery are selected from corresponding materials that can be conventionally used in secondary batteries, and they will not be described in detail here.
[0102] The following describes the invention in conjunction with specific embodiments.
[0103] Example 1
[0104] Composite phosphate positive electrode material and preparation method thereof
[0105] The composite phosphate cathode material is LiMn 0.798 Fe 0.199 Ti 0.003 PO4. Its preparation method comprises the following steps:
[0106] ① Mixing of raw materials: 37.0 g of lithium carbonate, 69.6 g of manganese dioxide, 30.2 g of iron phosphate, and 92.0 g of diammonium phosphate were mixed, and then 18.3 g of glucose and 0.12 g of titanium dioxide were added;
[0107] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 10:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0108] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0109] Example 2
[0110] Composite phosphate positive electrode material and preparation method thereof
[0111] The composite phosphate cathode material is LiMn 0.698 Fe 0.299 Ti 0.003 PO4. Its preparation method comprises the following steps:
[0112] ① Mixing of raw materials: 37.0 g of lithium carbonate, 60.9 g of manganese dioxide, 45.2 g of iron phosphate, and 80.5 g of diammonium phosphate were mixed, and then 17.9 g of glucose and 0.12 g of titanium dioxide were added;
[0113] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 10:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0114] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0115] Example 3
[0116] Composite phosphate positive electrode material and preparation method thereof
[0117] The composite phosphate cathode material is LiMn 0.598 Fe 0.399 Ti 0.003 PO4. Its preparation method comprises the following steps:
[0118] ① Mixing of raw materials: 37.0 g of lithium carbonate, 52.2 g of manganese dioxide, 60.3 g of iron phosphate, and 69.0 g of diammonium phosphate were mixed, and then 17.5 g of glucose and 0.12 g of titanium dioxide were added;
[0119] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 10:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0120] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0121] Comparative Example 1
[0122] Composite phosphate positive electrode material and preparation method thereof
[0123] The composite phosphate cathode material is LiMn 0.798 Fe 0.199 Ti 0.003 PO4. Its preparation method comprises the following steps:
[0124] ① Mixing of raw materials: 37.0 g of lithium carbonate, 69.6 g of manganese dioxide, 30.2 g of iron phosphate, and 92.0 g of diammonium phosphate were mixed, and then 18.3 g of glucose and 0.12 g of titanium dioxide were added;
[0125] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 20:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0126] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0127] Comparative Example 2
[0128] Composite phosphate positive electrode material and preparation method thereof
[0129] The composite phosphate cathode material is LiMn 0.798 Fe 0.199 Ti 0.003 PO4. Its preparation method comprises the following steps:
[0130] ① Mixing of raw materials: 37.0 g of lithium carbonate, 69.6 g of manganese dioxide, 30.2 g of iron phosphate, and 92.0 g of diammonium phosphate were mixed, and then 18.3 g of glucose and 0.12 g of titanium dioxide were added;
[0131] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 10:1, a rotation speed of 500 rpm, and a ball milling time of 8 h to obtain a powdered precursor;
[0132] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0133] Comparative Example 3
[0134] Composite phosphate positive electrode material and preparation method thereof
[0135] The composite phosphate cathode material is LiMn 0.794 Fe 0.198 Ti 0.008 PO4. Its preparation method comprises the following steps:
[0136] ① Mixing of raw materials: 37.0 g of lithium carbonate, 69.6 g of manganese dioxide, 30.2 g of iron phosphate, and 92.0 g of diammonium phosphate were mixed, and then 18.3 g of glucose and 0.32 g of titanium dioxide were added;
[0137] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 20:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0138] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0139] Comparative Example 4
[0140] Composite phosphate positive electrode material and preparation method thereof
[0141] The composite phosphate cathode material is LiMn 0.8 Fe 0.2 PO4. Its preparation method comprises the following steps:
[0142] ① Mixing of raw materials: 37.0 g of lithium carbonate, 69.6 g of manganese dioxide, 30.2 g of iron phosphate, and 92.0 g of diammonium phosphate were mixed, and then 18.3 g of glucose was added;
[0143] ②Preparation of precursor: ball mill the above precursor mixture at a ball-to-material ratio of 20:1, at a rotation speed of 500 rpm, for 8 h, and repeat three times to obtain a powdered precursor;
[0144] ③ Sintering of the precursor: In an atmosphere of nitrogen or argon, heat the above powdered precursor to 550°C at a heating rate of 5°C / min and calcine at a constant temperature for 4 hours, then heat to 780°C at a heating rate of 5°C / min and calcine at a constant temperature for 10 hours. After cooling, the composite manganese iron lithium phosphate material is obtained.
[0145] Performance Testing
[0146] (I) The powdered precursors and finished products of the composite phosphate-based positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were analyzed by scanning electron microscopy, and the finished product particles were analyzed by transmission electron microscopy; and the D 50 Particle size, D 90 Particle size; determine the compacted density and other properties of the finished particles.
[0147] (ii) The composite phosphate positive electrode material prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was used as the active material of the positive electrode sheet of the secondary battery to prepare a button battery. The specific preparation method of the button battery comprises the following steps: 90 g of the composite phosphate positive electrode material prepared according to the above method, 10 g of the conductive agent, and 10 g of the binder were added to 80 g of N-methylpyrrolidone solution (NMP solution), and stirred in a vacuum mixer for 2 hours to prepare a positive electrode slurry. The slurry was evenly coated on an aluminum foil, and then placed in a vacuum drying oven at 115°C for 13 hours, and cut to obtain a positive electrode sheet. The positive electrode sheet, the negative electrode sheet (metal lithium sheet with a diameter of 14.5 mm), the diaphragm (Celgard 2400 microporous polypropylene membrane) and the electrolyte (1 mol / L LiPF6 / EC+DMC (volume ratio 1:1)) were assembled into a CR2025 type button lithium ion battery in a glove box filled with hydrogen.
[0148] The electrochemical performance tests of the lithium-ion battery prepared above were carried out at 25° C. and 0.1C, including charge and discharge specific capacity, average voltage, efficiency, etc.
[0149] Results Analysis
[0150] (I) The powdered precursors and finished products of the composite phosphate-based positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were analyzed using a scanning electron microscope. The scanning electron microscope analysis images are as follows: Figure 1 to Figure 7As shown in Table 1, it can be seen that the composite phosphate-based positive electrode materials obtained in Examples 1 to 3 are uniform in size, and the particle coating layer is moderate and uniform, which helps to improve the electronic conductivity of the material; the compaction density of each finished particle is measured, as shown in Table 1, and the compaction density of the finished particles obtained in Examples 1 to 3 is 2.37 g / cm 3 , 2.41g / cm 3 , 2.40g / cm 3 The compacted density of the finished particles obtained in Comparative Examples 1 to 4 is substantially lower than 2.21 g / cm 3 It can be seen that the preparation method of the present application can control the particle size of the prepared finished particles by controlling the particle size of the powdered precursor and the normal distribution of the particles, and is beneficial to improving the compaction density of the material.
[0151] The powdered precursors of the embodiments and comparative examples were further analyzed to determine the D 50 Particle size and D 90 Particle size, as shown in Table 1, and combined Figures 1 to 8 As shown. It can be analyzed that in Example 1, the D 50 The particle size is 0.59 μm, D 90 The particle size is 2.34 μm, and the overall particle size is normally distributed; in Example 2, the D 50 The particle size is 0.57 μm, D 90 The particle size is 1.76 μm, and the overall particle size is normally distributed; in Example 3, the D 50 Particle size is 0.52μm, D 90 The particle size is 1.64 μm, and the overall particle size is normally distributed. 50 Particle size: 0.40 μm, D 90 The particle size is 0.66 μm, and the particle size of the precursor is too small. The finished product particles are small and easy to agglomerate. The reason is that during the ball milling process, the ball-to-material ratio is too high, the number of grinding balls is large, resulting in too high a grinding degree, and the product particle size cannot be controlled within the appropriate range. 50 The particle size is 2.4 μm, D 90 The particle size is 16.4 μm. The precursor particle size is not monitored in real time during the preparation process. The particle size of the precursor is non-normally distributed. Therefore, the compaction density of the finished particles is small, and the carbon coating is thin and uneven, which affects the compaction density capacity of the material. 50 The particle size is 0.71 μm, D 90The particle size is 2.52 μm. In Comparative Example 3, the amount of doped Ti ions added is too much, the particles are difficult to grow, and the compaction density is low, and it is easy to generate impurities inside the lattice of the finished product, which will affect the capacity and rate performance of the material. In Comparative Example 4, no Ti ions are doped, and the D 50 The particle size is 0.54 μm, D 90 The particle size is 1.94 μm; its precursor is not normally distributed and the compaction density is low, which will affect the electrochemical properties of the finished material.
[0152] Table 1
[0153] sample <![CDATA[Compaction density (g / cm 3 )]]> <![CDATA[Precursor D 50 (μm)]]> <![CDATA[Precursor D 90 (μm)]]> Example 1 2.37 0.59 2.34 Example 2 2.41 0.57 1.76 Example 3 2.40 0.52 1.64 Comparative Example 1 2.09 0.40 0.66 Comparative Example 2 2.21 2.4 16.4 Comparative Example 3 2.11 0.71 2.52 Comparative Example 4 2.20 0.54 1.94
[0154] Furthermore, the finished particles of Examples 1 to 3 and Comparative Examples 1 to 4 were analyzed using a transmission electron microscope; Figures 9 to 15 As shown in Table 2, the thickness of the carbon layer is measured by transmission electron microscope photos of lithium manganese iron phosphate particles. In each embodiment, more than a dozen different locations are selected for measurement in order to observe and verify the thickness and uniformity of the coating layer of the particles. The obtained data are shown in Table 2. Figures 9 to 15 From the analysis of the carbon layer thickness in Table 2, it can be seen that in the samples of Examples 1 to 3, the carbon layer is coated evenly and has a moderate thickness of 1.66 to 2.3 nm, with a variance of 0.03 to 0.23. It can be seen that the obtained finished particles have a good carbon coating effect and a moderate thickness, which is conducive to improving the material capacity. In contrast, in Comparative Examples 1 to 4, the carbon coating layer of the obtained material is uneven, thicker in some places and thinner in some places, with poor uniformity and poor carbon coating quality, which will affect the electrochemical properties such as the specific capacity of the overall material.
[0155] Table 2
[0156]
[0157]
[0158] (II) The prepared lithium-ion batteries were tested for electrochemical performance such as charge and discharge specific capacity, average voltage, and efficiency at 25°C and 0.1C, as shown in Table 3 and Fig.16 As shown, it can be seen that the lithium ion batteries prepared by the composite phosphate positive electrode materials prepared by the preparation method of the present application in Examples 1 to 3 can show better discharge specific capacity at 0.1C, wherein the lithium ion battery of Example 1 has a discharge specific capacity of 146.5 mAh / g at 0.1C, the lithium ion battery of Example 2 has a discharge specific capacity of 152.3 mAh / g at 0.1C, and the lithium ion battery of Example 3 has a discharge specific capacity of 154.1 mAh / g at 0.1C.
[0159] Table 3
[0160]
[0161]
[0162] According to the above analysis, the particle size and distribution of the precursor particles have a significant impact on the particle size and compaction density of the finished product, which is specifically manifested in: Compared with D 90 Precursor particles in the range of 1.0μm-3.0μm, D 90 When it is less than 1.0 μm, the primary particle size of the finished particles will be reduced by about 100 nm, and the discharge specific capacity of the material will be improved to a certain extent; when the particle size distribution of the precursor is greatly different from the normal distribution, the size distribution of the particles is poor, resulting in serious agglomeration of the finished particles and unclear boundaries, which are all unfavorable for the improvement of the compaction density of the material. When the precursor particles are well distributed, the carbon coating thickness of the obtained finished product is moderate and uniform: when the carbon coating layer is thicker, the transmission of lithium ions is hindered to a certain extent; when the carbon coating thickness is thin and uneven, it will cause the electrolyte to directly contact with LMFP, increase the side reaction and cause the loss of capacity, so the LMFP material in the present invention, its carbon coating layer helps its capacity to play. In addition, doping also has a significant effect on the capacity play and particle size of the material: within the appropriate doping range, the material can take into account the compaction density and capacity play; under excessive doping, although the specific capacity of the material is high, its particles and compaction density are at a lower level; and too low doping or no doping is very unfavorable to the performance of the material capacity.
[0163] In summary, the composite phosphate-based positive electrode material provided in the embodiments of the present application comprises a phosphate-based positive electrode material core and a carbon coating layer, wherein the particles of the composite phosphate-based positive electrode material are normally distributed, the finished particles are relatively large and the particle size is uniform, and the compaction density is significantly improved; and, the carbon coating layer is uniformly coated on the surface of the core material, and the thickness of the carbon coating layer is moderate, which can not only improve the electronic conductivity of the positive electrode material, but also improve the electrochemical properties of the composite phosphate-based positive electrode material, such as the discharge capacity and coulombic efficiency.
[0164] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite phosphate positive electrode material, characterized in that: It comprises a phosphate-based positive electrode material core and a carbon coating layer, wherein the particle size of the composite phosphate-based positive electrode material is normally distributed, the thickness of the carbon coating layer is 2.0-3.0 nm, and the variance is 0.01-0.
30.
2. The composite phosphate positive electrode material according to claim 1, characterized in that: The chemical formula of the core of the phosphate-based positive electrode material is Li x Mn a Fe b M c PO4, 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1; M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
3. The composite phosphate positive electrode material according to claim 1 or 2, characterized in that: The particle size of the composite phosphate positive electrode material is 180-230 nm, and the compaction density is greater than 2.37 g / cm 3 .
4. A method for preparing a composite phosphate positive electrode material, characterized in that: The steps include: Providing a precursor mixture of composite phosphate-based cathode materials; Ball-milling the precursor mixture to obtain a powdered precursor, and monitoring the particle size of the powdered precursor in real time until the particle size is normally distributed; The powdered precursor is subjected to a two-stage sintering treatment to obtain a composite phosphate-based positive electrode material.
5. The method for preparing a composite phosphate positive electrode material according to claim 4, characterized in that: The step of ball milling the precursor mixture to obtain a powdered precursor comprises: ball milling the precursor mixture for multiple times according to a ball-to-material ratio of 5:1 to 15:1 and performing real-time monitoring to control the particle size of the powdered precursor to be normally distributed, and the particle size D 90 1.0~3.0μm; And / or, the ball milling treatment is performed at a rotation speed of 450-650 rpm, for 7-8 hours, for 3-5 times, and with a grinding ball diameter of 6-7 mm.
6. The method for preparing a composite phosphate positive electrode material according to claim 4, characterized in that: The step of subjecting the powdered precursor to a two-stage sintering treatment includes: providing an inert gas atmosphere, heating the powdered precursor to 520-560°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 2-5 hours, and then heating to 720-780°C at a heating rate of 3-8°C / min and calcining at a constant temperature for 8-12 hours.
7. The method for preparing a composite phosphate positive electrode material according to claim 4, characterized in that: The step of providing a precursor mixture of a composite phosphate-based positive electrode material comprises: x Mn a Fe b M c PO4 obtains a lithium source, a manganese source, an iron source, a phosphorus source, and an M source, and then mixes them with a carbon source to obtain a precursor mixture; wherein M includes any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce; 0.9≤x≤1, 0.6≤a<1, 0.4<b<1, 0.001≤c≤0.004, and a+b+c=1.
8. The method for preparing a composite phosphate positive electrode material according to claim 7, characterized in that: The lithium source is any one of lithium carbonate, lithium acetate and lithium hydroxide; and / or, The manganese source is at least one of manganese dioxide, manganese tetraoxide and manganese oxalate; and / or, The iron source is at least one of ferric phosphate, ferrous nitrate, ferrous oxalate dihydrate and ferrous sulfate; and / or, The phosphorus source is at least one of ferric phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; and / or, The M source includes an oxide containing an M element; and / or, The carbon source is at least one of glucose, polyethylene glycol, citric acid, sucrose, glycine and starch; and / or, Taking the total mass of the precursor mixture as 100%, the added amount of the carbon source is 5-10wt%.
9. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the composite phosphate positive electrode material described in any one of claims 1 to 3 or the composite phosphate positive electrode material prepared by the preparation method of the composite phosphate positive electrode material described in any one of claims 4 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the positive electrode sheet according to claim 9.
Citation Information
Cited By
Positive electrode material, preparation method thereof and secondary battery
CN120709315A
Composite phosphate-based positive electrode material, preparation method therefor, and use thereof
WO2026065988A1